Handbook of Research on Creativity 2013
DOI: 10.4337/9780857939814.00044
|View full text |Cite
|
Sign up to set email alerts
|

What’s stopping us? Barriers to creativity and innovation in schooling across Europe

Abstract: IntroductionTheoretical definitions of creativity influence how and to what extent it is valued pedagogically and hence the usefulness awarded to innovation in the classroom. If it is seen as a realm for young geniuses, removed from the everyday of learning situations, then creativity becomes an elite affair and not the remit of most teachers. Similarly, if pedagogic innovation in teaching is something that requires an enormous infrastructure of new technological tools, then its absence can be blamed on the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Previous studies indicate that teachers value student creativity and generally hold positive attitudes toward TfC (Huang et al, 2019b; Bereczki & Kárpáti, 2018; Mullet et al, 2016). However, others have suggested that TfC encounters implementation difficulties in teaching practice (Al-Nouh et al, 2014; Banaji et al, 2013; Hong & Kang, 2010; Scott, 2015). Therefore, there is an urgent need to examine the factors that can promote TfC in the classroom (Bereczki & Kárpáti, 2018; Rubenstein et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies indicate that teachers value student creativity and generally hold positive attitudes toward TfC (Huang et al, 2019b; Bereczki & Kárpáti, 2018; Mullet et al, 2016). However, others have suggested that TfC encounters implementation difficulties in teaching practice (Al-Nouh et al, 2014; Banaji et al, 2013; Hong & Kang, 2010; Scott, 2015). Therefore, there is an urgent need to examine the factors that can promote TfC in the classroom (Bereczki & Kárpáti, 2018; Rubenstein et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…"Inibição", "timidez" e "falta de motivação" foram relatados em ordem de importância como barreiras enfrentadas pelos estudantes secundários gregos. Estas também foram frequentemente reconhecidas anteriormente como barreiras aos esforços de criatividade na literatura (ALENCAR, 2001;ALENCAR;FLEITH;MARTINEZ, 2011;BANAJI;CRANMER;PERROTTA, 2013;KONSTANTINIDOU et al, 2015;MORAIS et al, 2014). Os estudantes tendem a se sentir tímidos e inibidos para expressar suas ideias criativas se souberem que as ideias criativas não seriam compreendidas e apreciadas pelos professores.…”
Section: Discussionunclassified
“…However, barriers to successful teacher innovation and creative classroom learning practices across European schools fall into varying categories arising from political, policy, curriculum, and economic structures. These include functionalist summative testing, teacher or school target regimes, orthodox transmission methods of learning, analogue uses of digital technologies alongside philosophical or ideological mindsets (Banaji et al, 2013). Arguably, this can affect teacher confidence in the creative arts and therefore pupil learning opportunities.…”
Section: The Relationship Between Policy Curriculum and Pedagogymentioning
confidence: 99%